Assessing The Effects of Intergovernmental Fiscal Transfers on Public Service Delivery in Education and Health: A Case Study of Indonesia - Ariestiningtyas, Dewanti Rahma; Ananda, Candra Fajri; Sumantri, Vietha Devia Sagita (International Journal of Social Science and Business, 2024)
Indonesia still faces high inequality in both social and economic indicators. A component of fiscal transfers from the central government to the regions that focus on reducing inequality is the General Allocation Fund. One of the General Allocation Fund's objectives is to reduce inter-regional public service inequality. This study is critical because it aims to analyze the relationship between the General Allocation Fund and the provision of public services, especially in the education and health sectors. Using a dynamic panel data approach, this study finds that the General Allocation Fund positively affects the provision of public services in education and health, both in the short term and the long term. This is supported by developments in education and health that continue to improve, especially in terms of facilities, infrastructures, and human resources. However, despite this improvement, many records of inequality still occur in Indonesia, especially the disparities in Eastern Indonesia. Therefore, the government needs to focus its fiscal decentralization policy on increasing allocations based on the specific needs of each region. Continuous monitoring and evaluation should be implemented to ensure the effectiveness of the General Allocation Fund's utilization.